Reduction of orbital angular momentum radio beam divergence using a 3D printed planar graded index lenses - Allen, B; Drysdale, T; Zhang, S; Isakov, D; Tennant, A; Whittow, W; Stevens, C; Vardaxoglou, J; Coon, J (Institute of Electrical and Electronics Engineers, 2018)
This paper shows that the range of an Orbital Angular Momentum (OAM) radio link can be at least doubled by using a 3D graded index lens to reduce beam divergence. This is a major step towards realizing practical high capacity OAM radio links using cheap, compact and light weight lenses.